Application of Computer Digital Technology and Group Psychological Counseling in Higher Vocational Education Mental Health Education Curriculum under Complex Network Environment. (3rd June 2022) - Han, Yun
Abstract : Today's civilization is a network, with networks covering and organizing it. The important physical carrier of modern human social activities and interactions is a hybrid network formed by the interaction and integration of multiple networks, which is a dynamic and complex network. In the network environment, the mode and efficiency of information dissemination have changed qualitatively, which in turn profoundly affects the evolution of higher vocational education students' attitudes toward things and their psychological states. At present, there are many problems and difficulties in mental health education in higher vocational education institutions: there are misunderstandings in setting curriculum teaching objectives, teaching methods are not flexible enough, the professionalism and stability of teachers need to be improved, and the follow-up of mental health education for students in schools is insufficient. For this reason, we should take active measures to improve the effectiveness of mental health education in higher vocational education institutions according to the characteristics of the times, establish reasonable mental health education curriculum objectives and evaluation methods, establish diversified teaching methods to adapt to the complex network environment, build a professional mental health education teacher team, actively improve the teaching concept of mental health education, and focus on strengthening mental health education counseling in the process of entrance education and career guidance. This paper proposes a method based on computer digital technology and group counseling in a complex network environment, which can be applied to higher vocational education mental health education courses, and the experimental results show that the designed method has a high accuracy rate and provides support for higher vocational education students' psychological education and counseling.